Effect of FC3R on the properties of ultra-high-performance concrete with recycled glass (2019)
Ultra-high-performance concrete (UHPC) is the essential innovation in concrete research of the recent decades. However, because of the high contents of cement and silica fume used, the cost and environmental impact of UHPC is considerably higher than conventional concrete. The use of industrial byproducts as supplementary cementitious materials, in the case of recycled glass powder and fluid catalytic cracking catalyst residue (FC3R), as partial substitution of cement and silica fume allows to create a more ecological and cost-efficient UHPC. This research presents a study to determine the possibility of partial substitution of cement by FC3R in a previously optimized mixture of ultra-high-performance concrete with recycled glass. The results demonstrate that compressive strength values of 150 and 151 MPa without any heat treatment can be achieved, respectively, when replacing 11% and 15% of the cement with FC3R, for a determined amount of water and superplasticizer, compared to 158 MPa obtained for the reference UHPC without any FC3R content. The rheology of fresh UHPC is highly decreased by replacing cement particles with FC3R.